Educação escolar indígena: um estudo do diálogo entre os saberes indígenas e o conhecimento escolar no currículo em ação nas escolas indígenas - Almeida, Edielso Manoel Mendes de (2019)
This research presents INDIGENOUS EDUCATION as a subject: a study of the dialogue between indigenous knowledge and school knowledge in the curriculum in action in indigenous schools, in which we investigate the critical intercultural pedagogical practices developed by non - indigenous teachers of the Modular Teaching Organization System Indigenous Wajãpi (SOMEI / WAJÃPI) that has dialogue as a fundamental element. The objective of this study was to analyze the pedagogical practices developed by non - indigenous teachers who work in the final years of elementary school in SOMEI / WAJÃPI, based on the dialogue between indigenous knowledge and school knowledge from a critical intercultural perspective. It was a qualitative research of the ethnographic type, carried out with non-indigenous teachers who work from the 6th to the 9th year of elementary education in the state indigenous schools of the Wajãpi ethnic group located in the Indigenous Lands of that ethnic group in the State of Amapá. It was based on theoretical foundation: Catherine Walsh's conception of critical interculturality and the dialogue in Paulo Freire's conception. The results indicated that, even acting in a context of domination that characterizes the colonizing education based mainly on the dominant cultural and epistemological imposition, the investigated teachers were able to develop pedagogical practices based on the dialogue and the recognition of the indigenous knowledge that entered the curriculum of the disciplines , sometimes in a disciplinary way, others in an interdisciplinary way, with the active participation of students in the teaching and learning process. In such pedagogical practices, scholarly knowledge spoke horizontally, as Paulo Freire affirms, with indigenous knowledge, and was seen, valued and recognized as knowledge that guides the life of the Wajãpi in social, religious, cultural and productive activities